Defining the older patient population that require, but do not undergo emergency laparotomy: an observational cohort study protocol - Reeves, Nicola; Chandler, Susan; McLennan, Elizabeth; Price, Angeline; Boyle, Jemma; Knight, Stephen; Pearce, Lyndsay; Moug, Susan (International Journal of Clinical Trials, 2021)
Background: Despite older adults (65 years and above) accounting for almost half of emergency laparotomies and an ageing population, there remains a paucity of research in the older adult emergency surgery population. One key clinical area that requires urgent assessment is the older patient who presents with acute abdominal pathology treatable by laparotomy, but who does not undergo surgery (NoLAP). Methods: This multicentre prospective cohort study [defining the denominator: emergency laparotomy and frailty study 2 (ELF2)] will recruit consecutive older adults that require but do not undergo emergency laparotomy (NoLAP). We will recruit from 47 national health service hospitals over a 3-month timeframe. The same criteria as NELA for inclusion and exclusion will be applied. The primary aim is 90-day mortality. Secondary aims include characterisation of the NoLAP group, frailty and sarcopenia with comparison to those older adults that have undergone emergency laparotomy (ELAP). Decision-making will also be explored. Assuming a NoLAP rate of 32% and 10% dropout, a minimum of 700 patients are required for 95% power (alpha=0.05). Conclusions: The UK national emergency laparotomy audit has provided vital information on those patients undergoing emergency laparotomy and driven standards in operative and perioperative care. However, little is known of outcomes in those patients who do not undergo emergency laparotomy. Improved understanding of this NoLAP population would aid shared decision-making and improve standards for this otherwise poorly understood vulnerable patient group. Trial registration: This study is registered online at www.clinicaltrial.gov (Reg number: ISRCTN14556210).